Karakteristik dan Perilaku Caregiver Lansia dengan Comorbid dalam Pencegahan Infeksi Covid-19 - Irwadi Irwadi; Arina Widya Murni; Elvi Oktarina (Universitas Batanghari Jambi, 2021)
Providing education in the prevention of COVID-19 infection is an effort to reduce morbidity and mortality in the elderly. However, after health education was carried out on elderly caregivers, the incidence of COVID-19 was still high. This research is a descriptive study that aims to explore the characteristics and behavior of elderly caregivers in preventing COVID-19 infection. This is done to be able to plan the provision of further interventions to the elderly caregiver. The sampling technique used non-probability methods with a total sampling technique totaling 76 respondents. The research instrument used KAP (Knowledge, Attitudes, and Practices) with a total of 32 questions, Cronbach alpha knowledge (0.834), attitude (0.791), and action (0.828). Data analysis using univariate analysis. Characteristics of respondents at the age of 18-40 years (86.8%), the most gender is female (94.7%), most education is high school (63.1%) and the relationship between caregiver and the elderly is (84.2%). The mean value of knowledge is 7.55, attitude is with a mean value of 26.24, and action is with a mean value of 27.21. Based on the conclusion, the results of research on the behavior of elderly caregivers with comorbidities in the prevention of COVID-19 infection are related to the inadequate risk factors for infection with COVID-19 so that it can cause the elderly to have the risk of being infected with COVID-19.